A participaç\~ao do Brasil nas operaç\~oes de paz das Naç\~oes Unidas: Evoluç\~ao, desafios e oportunidades - Israel de Oliveira Andrade; Eduarda Passarelli Hamann; Matheus Augusto Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– Based on a state policy perspective, this paper presents the path of Brazil's participation in U.N. peace operations, from its genesis in 1947 to the present day, with the intent to comprehend if there is in fact a progressive and evolutionary pattern in the participation of Brazil in peacekeeping, and which would be the challenges, contributions and future orientations to the country in this matter. For that, in a first moment, the text will bring a conceptual discussion regarding the different definitions and understandings on peacekeeping operations. Subsequently, we will analyze the evolution of UN peacekeeping operations throughout its 70 years and the Brazilian positions during this period. In a third moment, we will present the final considerations identifying the upcoming challenges and the main possible perspectives for Brazil to engage in future peacekeeping operations. The intention, therefore, is to ascertain whether peacekeeping operations, as an instrument of international policy aligned to the guidelines of Brazilian defense policy and foreign policy, should continue to be supported by Brazil or if new reorientations are necessary as a national strategy.
Keywords: F02; F51; F52; 330; peace operations; Brazil; United Nations; MINUSTAH; UNIFIL; peacekeeping